Maternal and Perinatal Outcome in Gestational Diabetes Mellitus Compared to Pregestational Diabetes Mellitus (BIRDEM Medical Journal, 2019)
Background: Diabetes mellitus is the most frequently encountered endocrine disorder in pregnancy and is associated with adverse outcomes if remain undiagnosed or untreated. This study was done to compare the maternal and perinatal outcome of pregestational diabetes mellitus (PGDM) with that of gestational diabetes (GDM).Methods: This observational analytical study with group comparison was carried out in the Department of Obstetrics and Gynaecology, BIRDEM General Hospital, Dhaka from July 2015 to June 2016. This study was conducted on two groups of pregnant women: group A (PGDM) and group B (GDM). A total of 100 cases were selected and in each group 50 pregnant women were enrolled. Singleton pregnancy and age 18 to 45 years were included. Pregnancy with hypertension, heart disease, renal disease and other metabolic disorders were excluded.Results: In this study mean gestational age of the study subjects were 35.72 ± 2.61 weeks and 36.58 ± 2.34 weeks in PGDM and GDM groups. History of GDM [34.0% vs 16.0%], intrauterine death (IUD) [14.0% vs 2.0%] and abortion [22.0% vas 6.0%] were significantly higher among PGDM patients than GDM patients. Regarding present pregnancy complications, polyhydramnios [32.0% vs 14.0%], preterm delivery [38.0% vs 20.0%], vulvovaginitis [28.0% vs 12.0%] and premature rupture of membrane (PROM) [24.0% vs 8.0%] were significantly higher in PGDM than GDM patients. Wound infection was significantly high in PGDM groups [35.7% vs 11.1%] among the patients delivered by lower uterine Cesarean section (LUCS). Regarding perinatal complications, hypoglycemia [22.0% vs 8.0%], birth asphyxia [24.0% vs 8.0%], RDS [24.0% vs 8.0%] were significantly higher among PGDM comparing GDM patients.Conclusion: The maternal and perinatal outcomes of pregestational diabetes mellitus were less favorable than those of gestational diabetes mellitus.Birdem Med J 2019; 9(2): 127-132